Psychological Barriers and Their Relationship in Cope with University Life at University' Students (Journal of the College of Education for Women, 2019)
Current Thesis has aimed to identify : The Psychological barriers for university students , Differences in psychological barriers depending on the variable sex (Males – Females) , Adjustment to College life for university students, Differences in Adjustment to College at university life depending on the variable sex (Males – Females), and finally, The correlation between psychological barriers and Adjustment to College life. The researcher has prepared a sample consisted of (100) male and female students who were randomly selected from university students, The researcher has adopted a measure of (2002) to measure the psychological barriers, also the researcher adjustment scale with university life.The results showed that university students have psychological barriers and there is no difference between males and females in this scale, and there is an adjustment with university life, males had more adjustment than females.Thus, the results showed there was no correlation function between the psychological barriers and Adjustment to College ..Through this research , results appeared a number of recommendations and proposals.